A frictionless and secure user authentication in web-based premium applications - Olanrewaju, Rashidah Funke; Khan, Burhan Ul Islam; Morshidi, Malik Arman; Anwar, Farhat; Mat Kiah, Miss Laiha (IEEE, 2021)
By and large, authentication systems employed for web-based applications primarily utilize conventional username and password-based schemes, which can be compromised easily. Currently, there is an evolution of various complex user authentication schemes based on the sophisticated encryption methodology. However, many of these schemes suffer from either low impact full consequences or offer security at higher resource dependence. Furthermore, most of these schemes don’t consider dynamic threat and attack strategies when the clients are exposed to unidentified attack environments. Hence, this paper proposes a secure user authentication mechanism for web applications with a frictionless experience. An automated authentication scheme is designed based on user behavior login events. The uniqueness of user identity is validated in the proposed system at the login interface, followed by implying an appropriate user authentication process. The authentication process is executed under four different login mechanisms, which depend on the profiler and the authenticator function. The profiler uses user behavioral data, including login session time, device location, browser, and details of accessed web services. The system processes these data and generates a user profile via a profiler using the authenticator function. The authenticator provides a login mechanism to the user to perform the authentication process. After successful login attempts, the proposed system updates database for future evaluation in the authentication process. The study outcome shows that the proposed system excels to other authentication schemes for an existing web-based application. The proposed method, when comparatively examined, is found to offer approximately a 10% reduction in delay, 7% faster response time and 11% minimized memory usage compared with existing authentication schemes for premium web-based applications.